2011
DOI: 10.4238/2011.october.18.2
|View full text |Cite
|
Sign up to set email alerts
|

Short Communication Isolation and characterization of polymorphic microsatellite loci in Aleurodicus dispersus (Hemiptera, Aleyrodidae)

Abstract: ABSTRACT. Ten microsatellite markers were isolated and characterized from Aleurodicus dispersus, the spiraling whitefly, an exotic pest species that is considered to be one of the most serious agricultural pests on Hainan Island, China. The polymorphism of these loci was examined in individual whiteflies from Hainan Island and from the Canary Islands. All loci were polymorphic, with two to four alleles per locus. Mean observed and expected heterozygosity values were 0.773 and 0.585, respectively. These microsa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 5 publications
(3 reference statements)
1
2
0
Order By: Relevance
“…Similar results were reported by Ma et al (2011) who observed that microsatellite markers had heterozygosity from Hainan and Canary Island, which ranged from 0.100 to 0.933. Several studies have been carried out to characterize the extent of genetic diversity and differentiation of whitefly populations (Rekha et al 2005;De Barro 2005;Chu et al 2007;Tsagkarakou et al 2007).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Similar results were reported by Ma et al (2011) who observed that microsatellite markers had heterozygosity from Hainan and Canary Island, which ranged from 0.100 to 0.933. Several studies have been carried out to characterize the extent of genetic diversity and differentiation of whitefly populations (Rekha et al 2005;De Barro 2005;Chu et al 2007;Tsagkarakou et al 2007).…”
Section: Discussionsupporting
confidence: 92%
“…SSR markers have been used to differentiate B. tabaci variants and to estimate the biotypes and genetic relationships of closely related populations from the same geographical location (De Barro et al 2003;Tsagkarakou et al 2007;Gauthier et al 2008). The primer sequences of around 10 SSR markers are publicly available for studying the A. dispersus genome (Ma et al 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation